Effects of Economic Conditions and Policy Interventions on OECD Broadband Adoption - Bauer, J.; Madden, Gary; Morey, A. (Taylor & Francis, 2014)
The positive effects of broadband networks and services on productivity and economic growth are well established. Looking at broadband as an engine of economic prosperity, the OECD and its member states are seeking to foster its widespread adoption. However, which public policies best promote the adoption of broadband remains controversial. This article contributes in two ways to this discussion. It offers a comprehensive discussion of the factors that influence broadband adoption and uses an econometric approach that is well-suited to overcome the challenges of modelling broadband adoption. This framework allows drawing more robust and nuanced policy recommendations.